Kebijakan Pengembangan Usaha Kelompok Tenun Tradisional di Desa Monta Baru Kecamatan Lambu Kabupaten Bima - Taufik Irfadat; Rifai Ahmad; Junaidin Junaidin (Program Studi Administrasi Negara Universitas Serang Raya, 2022)
This study aims to determine the level of development of the traditional weaving group activities in Monta Baru Village, while the data collection techniques are interviews, observation, and documentation. Then the results of the research are the efforts of the new monta village government to develop a traditional weaving business which is given to 3 (three) groups in the new monta village with a total budget of Rp. 60,000,000, - with the division that each group gets a budget of Rp. 20,000,000,- with the stimulation of this fund, it can provide sufficient capital injection for the weaving group in the village of Monta Baru. A sheet of sarong takes 3 (three) days, this is because the production process is still traditional and requires a high level of focus and precision. The production of a sheet of sarong takes a long time and varies as the difficulty level gets higher. Marketing is still carried out between individual buyers and bought up by clothing sellers, sometimes marketing is done by means of social gathering. Village Head Regulation Number 4 of 2018 concerning improving the competence of weaving groups.